2012
DOI: 10.3109/s10165-011-0544-2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is associated with an increased risk of developing ACPA-positive but not ACPA-negative rheumatoid arthritis in Asian populations: evidence from the Malaysian MyEIRA case–control study

Abstract: We investigated the association between cigarette smoking and the risk of developing rheumatoid arthritis (RA) in the Malaysian population. A total of 1,056 RA patients and 1,416 matched controls aged 18-70 years within a defined area of Peninsular Malaysia were evaluated in a case-control study between August 2005 and December 2009. A case was defined as a person with early diagnosed RA using the 1987 American College of Rheumatology criteria for RA. Controls were randomly selected matched for sex, age, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Of the 10 studies that met the predefined inclusion criteria, 4 were from North America [4,14,16,20], 5 from Europe [2,5,21,22,24], and 1 from Malaysia [23], and they included a total of 181 100 subjects and 4,552 RA cases (Table 1). The median of the highest category of number of pack-years analyzed in each study ranged between 15 and more than 55 pack-years, while the reference group for all studies was never smokers.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies that met the predefined inclusion criteria, 4 were from North America [4,14,16,20], 5 from Europe [2,5,21,22,24], and 1 from Malaysia [23], and they included a total of 181 100 subjects and 4,552 RA cases (Table 1). The median of the highest category of number of pack-years analyzed in each study ranged between 15 and more than 55 pack-years, while the reference group for all studies was never smokers.…”
Section: Resultsmentioning
confidence: 99%
“…Malays, Chinese, and Indians). The details of the MyEIRA study have been described elsewhere [3, 17]. In brief, patients with early RA were identified from nine rheumatology centers throughout Peninsular Malaysia, and for each case, a population control was randomly selected matched by age, sex, and residential area.…”
Section: Methodsmentioning
confidence: 99%
“…One example of this is the shared epitope (SE) alleles of the human leukocyte antigen DR beta chain 1 (HLA-DRB1), which is a major risk factor for ACPA-positive RA, but not to the same extent for ACPA-negative RA. Environmental/lifestyle factors, such as smoking [13] and other noxious airway exposures [4, 5], have been shown to be risk factors for RA, mainly for the ACPA-positive subset of RA.…”
Section: Introductionmentioning
confidence: 99%
“…In early RA patients, smoking was associated with higher RA disease activity (number of tender joints, Larsen's score, DAS-28, higher frequency of autoantibodies), and severity independent of age, alcohol consumption, follow-up duration, and gender [23,24,30]. Prospective monitoring of 100 early RA patients for 2 years indicated that RA disease activity (swollen and tender joints, pain) increased stepwise from never smokers to former smokers to current smokers [31].…”
Section: Smoking's Effect On Ra Diseasementioning
confidence: 99%
“…Longer duration and higher intensity of smoking increased the risk of onset of RA [22], especially ACPA positive RA [23]. Smoking was associated with earlier age of onset of RA [24,25].…”
Section: Smoking's Effect On Ra Diseasementioning
confidence: 99%